![(6n+2)=n(3n+5)](https://img.qammunity.org/2023/formulas/mathematics/college/xq0egdah84ngvxl37le2qlvchrujgzhm85.png)
To prove if it is true for positive n intergers for induction method:
1. Prove For n=1
![\begin{gathered} (6(1)+2)=1(3(1)+5) \\ 6+2=3+5 \\ 8=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nccwbeibvvcbqpx555n3q9sibl3vjv4uk6.png)
For n=1 it is true
2. Assume that the statement is true for n=k.
It is true for n=k
3. Prove For n=k+1
![\begin{gathered} (6(k+1)+2)=(k+1)(3(k+1)+5) \\ 6k+6+2=(k+1)(3k+3+5) \\ 6k+8=(k+1)(3k+8) \\ 6k+8=3k^2+8k+3k+8 \\ 6k+8=3k^2+11k+8 \\ 6k+8\\e3k^2+11k+8 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/68dwd0e2bcmtftbrjh0gtwo03xpz2rv2v8.png)
As the conjeture is not true for n=k+1
The conjeture is not true for all positive intergers